Phagocytic and pinocytic uptake of cholesterol in Tetrahymena thermophila impact differently on gene regulation for sterol homeostasis - Hernández, Josefina (2021)
Fil: Fil: Herández, Josefina. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (CONICET). Argentina.